The Relationship Between Serum Ferritin Levels and Left Ventricular Function in Patients Undergoing Hemodialysis - Harahap, Astry Amelia; Nasution, Alwi Thamrin; Isnanta, Rahmat (Journal of Society Medicine, 2023)
Introduction: Left ventricular hypertrophy (LVH) is a common condition that often occurs in patients undergoing regular hemodialysis, and it is associated with a poor prognosis in these patients. The worsening of LVH symptoms in patients undergoing hemodialysis is the strongest predictor of sudden cardiac death in such individuals. The aim of this study was to determine the relationship between serum ferritin levels and left ventricular function in patients undergoing hemodialysis at RSUP Haji Adam Malik, Medan. Method: The design of this study is a cross-sectional study with consecutive sampling. The study population consists of patients undergoing regular hemodialysis, and the population includes patients who undergo regular hemodialysis in RSUP H. Adam Malik. Results: There was a significant relationship between hemoglobin, albumin, and serum ferritin levels with left ventricular function (p < 0.005). Hemoglobin showed a moderate positive correlation with LVEF (r = 0.477). The relationship between albumin and LVEF had a stronger correlation (r = 0.681). There was a strong and significant negative correlation between serum ferritin and LVEF (r = -0.961). Conclusion: A significant relationship was found between hemoglobin levels, albumin levels, mean serum ferritin level, and left ventricular function in hemodialysis patients. Hemoglobin and albumin showed a positive correlation with left ventricular function, while serum ferritin level had a significant and strong negative correlation with left ventricular function.